Deutsche Malerei : 1905-1930 : Informationsblätter V. - Wilhelm-Lehmbruck-Museum, Duisburg (Duisburg : Wilhelm-Lehmbruck-Museum, 1987)
Beckmann, Max ; Campendonk, Heinrich ; Dexel, Walter ; Ernst, Max ; Feininger, Lyonel ; Grosz, George ; Heckel, Erich ; Kirchner, Ernst Ludwig ; Kokoschka, Oskar ; Macke, August ; Molzahn, Johannes ; etc.
boek